Allelopathic Interaction of Spinach (Spinacia oleracea L.) with Trigonella and Coriandrum sativum - and Junaid Aslam2, M. Akmal1*, Vimala Y1 (Current Botany, 2011)
The negative allelopathic interaction of spinach with other crop plants (fenugreek and coriander) was studied under laboratory conditions. The seeds of Spinacia oleracea were grown in combinations with trigonella and coriander seeds in the seed extracts of all three plants in dilutions of 1:10, 1:20 and 1:50 and in distilled water as control. The seedling growth were studied in terms of radicle length, dry weight, total nitrogen and carbohydrate contents at 3rd and 7th day immediately after radicle emergence. It was found that the growth of spinach was inhibited by Trigonella and coriander seedlings. In their own seed extract the growth inhibition was not more as compared to distilled water grown control and with Trigonella or coriander seedlings. The total nitrogen and carbohydrate contents were lower in spinach seedlings grown in the seed extracts of Trigonella and Coriandrum both, as compared to control.Ã‚Â 